Magnetic, electron paramagnetic resonance, and photocatalytic analysis of diluted magnetic semiconductor CdS:V nanoparticles. Issue 11 (1st June 2021) - Poornaprakash, B.; Vattikuti, S.V. Prabhakar; Subramanyam, K.; Kumar, Mirgender; Kim, Y.L.; Pratap Reddy, M. Siva
Abstract: Diluted magnetic semiconductors related to II–VI-based compounds are of significant interest for the development of spin-based operating electronic devices such as magneto-optical instruments, spintronics, and nonvolatile memory devices. Thus, studies of electron paramagnetic resonance, magnetic characteristics, and the photocatalytic properties of transition metal-doped II–VI-based semiconductors are of great importance. We therefore comprehensively studied the structural, electron spin resonance, magnetic hysteresis, and photocatalytic characteristics of CdS:V 4+ nanoparticles (NPs) fabricated by the rapid microwave route for the first time. The structural analyses revealed the authentic substitution of V 4+ dopant ions into the CdS matrix. The widening of the optical band gap and relevant quantum confinement phenomenon are discussed in terms of the inclusion of V 4+ ions into the CdS matrix. The electron paramagnetic resonance (EPR) spectroscopy results were corroborated by the increase in the number of magnetic spins with increasing V 4+ dopant concentration. The assessed number of magnetic spins was nearly equal to 3.601597 × 10 6 and 7.254048 × 10 6 for the CdS:V (2 and 4 at%) NPs, respectively. Room-temperature magnetic hysteresis loops also revealed the existence of a large number of magnetic spins through the formation of clear paramagnetism in the CdS:V (2 and 4 at%) NPs. The CdS:V (4 at%) system displayed enriched visible light-driven photocatalytic degradation efficiency compared to bare CdS through the degradation of RhB dye in contaminated water.